A net-centric metadata framework for service-oriented environments. (11th November 2009) - Parmelee, Mary C.; Nichols, Deborah L.; Obrst, Leo
The US Department of Defense (DoD) Chief Information Office (CIO) has embarked on an enterprise data management transformation initiative known as the DoD Net-Centric Data Strategy (NCDS). NCDS-related directives require DoD components, such as the United States Air Force (USAF), to describe mission-critical information assets using shared metadata catalogues and metadata registries. To satisfy NCDS requirements, the USAF is transitioning to a service-oriented environment (SOE). The USAF Net-Centric Metadata Framework (NCMF) extends the NCDS notion of metadata and the information assets that it describes in order to support the USAF SOE. The NCMF is implemented in the USAF Metadata Environment (MDE), which enables enterprise-level semantic consistency by linking information asset metadata, service specification metadata, and ontologies. This paper presents the USAF Net-Centric Metadata Framework and its MDE implementation as a practical and potentially reusable approach for achieving semantically interoperable information sharing capability in an enterprise-scale SOE.